Late Holocene forest contraction and fragmentation in central Africa. Issue 1 (12th December 2017) - Maley, Jean; Doumenge, Charles; Giresse, Pierre; Mahé, Gil; Philippon, Nathalie; Hubau, Wannes; Lokonda, Michel O.; Tshibamba, John M.; Chepstow-Lusty, Alex
Abstract: During the warmer Holocene Period, two major climatic crises affected the Central African rainforests. The first crisis, around 4000 cal yr BP, caused the contraction of the forest in favor of savanna expansion at its northern and southern periphery. The second crisis, around 2500 cal yr BP, resulted in major perturbation at the forest core, leading to forest disturbance and fragmentation with a rapid expansion of pioneer-type vegetation, and a marked erosional phase. The major driver of these two climatic crises appears to be rapid sea-surface temperature variations in the equatorial eastern Atlantic, which modified the regional atmospheric circulation. The change between ca. 2500 to 2000 cal yr BP led to a large increase in thunderstorm activity, which explains the phase of forest fragmentation. Ultimately, climatic data obtained recently show that the present-day major rise in thunderstorms and lightning activity in Central Africa could result from some kind of solar influence, and hence the phase of forest fragmentation between ca. 2500 to 2000 cal yr BP may provide a model for the present-day global warming-related environmental changes in this region.